Assessment of Nurses' Knowledge, Attitude, and Practice on Oral Care for Intensive Care Unit Patients - Hend Miladi,; Eman Gusbi,; Jamal Elcosbi, (AlQalam Journal of Medical and Applied Sciences, 2026)
Maintaining oral hygiene for ICU patients is crucial for improving their overall health and avoiding complications. As the main providers of care, nurses need sufficient knowledge, positive attitudes, and proper practices to ensure effective oral care. This study aimed to assess nurses' understanding, perspectives, and methods regarding oral healthcare for ICU patients. The study sample was randomly selected from nurses at Tripoli Central Hospital, “Al-Zawiya Street” in Tripoli, and included 60 study participants, 28 of whom were males and 32 were females, with ages ranging from 18 to more than 50 years. And the sample was collected during the period June-July 2024. The data showed that the majority of participants were female (53%), and the highest age group was between 18-25 years (42%) and 25-35 years (42%). The highest age group of participants was less than 5 years (42%). 77% believed that they had sufficient experience in the field of nursing care, and 41% classified themselves as having obtained 9 out of 10. The results of the chi-square analysis on the questions related to knowledge, attitudes, and practice showed a statistical significance of 0.001 and positive answers, indicating that there is some awareness among nurses. The present study showed that nurses had positive attitudes, moderate knowledge, and reasonable practices regarding dental care. There is a need to include oral health training in nurses' education during their school years. Integration of oral health and public health should be a cornerstone of policy approaches for the prevention and control of oral diseases. A standard protocol should be developed in all health institutions.